Application Rule Base on Facial Skin Type Identification Expert System using Forward Chaining - Basir, Azhar; Tyas, Fitri Ayuning; Maghsyari, Yusril Ahzam (Sistemasi: Jurnal Sistem Informasi, 2024)
Most people, especially women, have a great desire to have white, healthy, clean and well-maintained facial skin. However, their knowledge about facial skin types is still limited, even though consulting with an expert requires a lot of time and money which results in someone not paying attention to facial skin type when carrying out treatment. Therefore, an expert system is needed that can help identify facial skin types. A rule base is a rule created based on expert knowledge needed to create an expert system. The forward chaining method is a search method or forward tracing technique that starts from existing information and combines rules to produce a conclusion or goal. The research results show that this application can run well and is suitable for use. Based on the results of system testing from an expert, it was concluded that identifying facial skin types based on facial skin criteria using the forward chaining method had an accuracy rate of 84% where the results of system testing produced several conclusions about the appropriate type of facial skin with the selected criteria data.